A PROSPECTIVE STUDY ON MODIFIED APPROACH TO CLASSICAL DACRYOCYSTORHINOSTOMY - AMIN, NIKUNJ; MAKWANA, KISHAN; GUPTA, ARUNA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Aim and Objective: The present study was done with an aim to present the outcome of the modified technique of external dacryocystorhinostomy (DCR) with anterior flap anastomosis with the excision of posterior flaps. Methods: Present prospective and observational study was carried out at C.U. Shah Medical College after taking permission from the ethical committee at C.U. Shah Medical College. A total of 100 participants were included in the study. All surgeries were performed by the same surgeon. All routine investigations including thorough rhinological checkup were carried out before DCR surgery. Patients were followed up for period of 1 year. Patency of lacrimal sac was considered as a successful result. Results: Review of complications demonstrates that only four cases had intraoperative hemorrhage more than 100cc, while 96 experienced less hemorrhage. Two patients had early post-operative hemorrhage in the form of epistaxis which stopped without need for nasal repacking. Another two patients had orbital hemorrhage without seriously elevating the intraocular pressure. There was no case of orbital emphysema, cerebrospinal fluid leakage, or wound sepsis in our study. Six patients had post-operative epiphora in varying degrees. Conclusion: Although it is simpler and easier to master the surgical technique, anterior single flap DCR shows a success rate comparable to that obtained by the more complex conventional DCR.